Durability properties of high volume fly ash concrete containing nano-silica - Supit, S.; Shaikh, Faiz (Springer Netherlands, 2014)
This paper reports the results of an experimental study on durability of ordinary concrete and high volume fly ash (HVFA) concrete containing nano silica (NS). In this study, concretes containing 2 and 4 %of NS are prepared at a constant water/binder ratio of 0.4 for testing ages of 3, 7, 28, 56 and 90 days. The concrete containing 2 % NS exhibited similar compressive strength of that containing 4 % NS and is used to evaluate its effectiveness in HVFA concrete. The compressive strength and durability tests including water sorptivity, volume of permeable voids (VPV), chloride permeability and porosity are investigated experimentally. Results show that besides improvement in compressive strength, the addition of 2 % NS significantly reduced the water sorptivity, VPV, chloride permeability and porosity of HVFA concretes. It is also revealed that the above durability properties of concretes containing 38 % class F fly ash and 2 % NS as partial replacement of cement are superior than ordinary concrete containing 100 % cement.